Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/v13030406
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Cell Culture System of Persistent Hepatitis E Virus Infection in the Human HepaRG Hepatic Cell Line

Abstract: Hepatitis E virus (HEV) is considered as an emerging global health problem. In most cases, hepatitis E is a self-limiting disease and the virus is cleared spontaneously without the need of antiviral therapy. However, immunocompromised individuals can develop chronic infection and liver fibrosis that can progress rapidly to cirrhosis and liver failure. The lack of efficient and relevant cell culture system and animal models has limited our understanding of the biology of HEV and the development of effective dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 84 publications
(115 reference statements)
2
9
0
Order By: Relevance
“…They reported that these in vitro culture systems support HEV replication and release of encapsulated RNA [43]. In accordance with this study, Pellerin and her colleagues showed that HepaRG is a relevant and efficient in vitro model of HEV replication that could be used to study HEV and identify effective antiviral drugs against chronic HEV infection [44]. Besides, another study introduced a new procedure using a cocktail of 5 chemicals (Forskolin, SB431542, IWP2, DAPT, and LDN193189), allowing fast differentiation and efficient HDV-infection of HepaRG cells [45].…”
Section: In Vitro Modelssupporting
confidence: 64%
See 1 more Smart Citation
“…They reported that these in vitro culture systems support HEV replication and release of encapsulated RNA [43]. In accordance with this study, Pellerin and her colleagues showed that HepaRG is a relevant and efficient in vitro model of HEV replication that could be used to study HEV and identify effective antiviral drugs against chronic HEV infection [44]. Besides, another study introduced a new procedure using a cocktail of 5 chemicals (Forskolin, SB431542, IWP2, DAPT, and LDN193189), allowing fast differentiation and efficient HDV-infection of HepaRG cells [45].…”
Section: In Vitro Modelssupporting
confidence: 64%
“…Primary cells Adult PHH [15,21] Adult PHH [17] Adult PHH [18][19][20][21] Adult PHH [18] primary human intestinal cells [23] primary human endometrial cells [24] Cancer cell lines HepAD38 [34] HepDE19 [35] Hepa RG [44,46] HLCZ01 [36] (HepNB2.7) [38] HrpaRG [39,40] HepG2 +Huh-7 [49,55] HepG2 [51] HepG2-NTCP [52] HLC [24,26,64] HLCZ01 [36] HepG2 [ [150] Abbreviations: ETV, entecavir; FRG, fumaryl acetoacetate hydrolase (Fah)/RAG2/interleukin (IL) 2-gammaC; FRGS, Fah −/− Rag2 −/− IL-2Rγc −/− SCID; HEV, hepatitis E virus; HBV, hepatitis B virus; HCV, hepatitis C virus; IFN, interferon; IG, immunoglobulin; NK, natural killer; NM23TC, nanoformulation of the modified lamivudine 3TC; PRI-724, selective inhibitor of β-catenin/CBP; RG7834, inhibitor of HBV expression; uPA/RAG-2, urokinase-type plasminogen activator/recombinant activation gene-2; uPA/SCID, urokinase-type plasminogen activator/severe combined immunodeficiency; WHBV, woodchuck hepatitis B virus; WMHBV, woolly monkey hepatitis B virus.…”
Section: Dmentioning
confidence: 99%
“…The RNA library was prepared for each RNA sample tested using Ion Total RNA-Seq kit v2 (Life Technologies, Carlsbad, CA, USA) and then sequenced using Ion Torrent Proton technology. The reads were cleaned with the Trimmomatic 0.36 software, followed by bioinformatics analysis as previously described (37,38) using the GenBank Mink Caliciviridae reference sequence MF677852.1 for the two swab RNA samples and the Mink coronavirus 1 reference sequence MN535737.1 for the fecal RNA sample to calculate sub-sampling and final alignment.…”
Section: Methodsmentioning
confidence: 99%
“…HepaRG cell culture: Human HepaRG™ cells were grown as previously described (Pellerin et al., 2021). Briefly, HepaRG were seeded into 6‐well plates (2 × 10 5 cells/well) and maintained in growth medium for 2 weeks.…”
Section: Methodsmentioning
confidence: 99%